Modification of Saccharomyces cerevisiae Cells with Metal Hexacyanoferrates for the Construction of a Yeast-Based Fuel Cell - Gabija Adomaitė; Povilas Virbickas; Aušra Valiūnienė (Molecules)
This research presents a simple procedure for chemically modifying yeast (Saccharomyces cerevisiae) cells with nickel hexacyanoferrate (NiHCF) and ferric hexacyanoferrate, also known as Prussian blue (PB), to increase the conductivity of the yeast cell wall. Using linear sweep voltammetry, NiHCF-modified yeast and PB-modified yeast (NiHCF/yeast and PB/yeast, respectively) were found to have better cell wall conductivity in [Fe(CN)6]3− and glucose-containing phosphate-buffered solution than unmodified yeast. Spectrophotometric analysis showed that the modification of yeast cells with NiHCF had a less harmful effect on yeast cell viability than the modification of yeast cells with PB. The use of NiHCF/yeast and PB/yeast cells in the construction of a yeast-based fuel cell allowed the maximum power densities of 62.66 mW/m2 and 94.09 mW/m2 to be achieved. These values were much higher than those obtained using unmodified yeast cells (42.25 mW/m2). NiHCF/yeast and PB/yeast fuel cells were renewed by replenishing the yeast suspension in the anolyte or the FeCl3 salt in the catholyte. This allowed 77.4% and 50.1% of the initial maximum power density of the fuel cells to be achieved.